Cholinesterase and glutathione-s-transferase activities in freshwater invertebrates as biomarkers to assess pesticide contamination - Domingues, I
Studies investigating the use of biomarkers in pesticide risk assessment have greatly increased in recent years; however, issues concerning the ecological meaning of enzymatic responses have proved controversial. Ideally a good biomarker response should be modulated by the environmental contaminants alone and demonstrate a predictable behavior towards certain types of toxins. As these premises are rarely observed, the present study aims to outline research that has contributed to an understanding of the behavior of two widely used biomarkers, cholinesterase and glutathione-S-transferase, describing environmental and biotic factors that affect their response in freshwater invertebrates. Studies were performed in the main classes of aquatic invertebrates with these biomarkers and conclusions were reached concerning their behavior towards the main classes of pesticides. Links between biomarker responses and conventional endpoints were evaluated so that ecological relevance could be attributed to enzymatic responses. Toxicity of mixtures was investigated, and cases of synergism and antagonism were pointed out as factors changing the expected toxicity of aquatic systems and leading to misinterpretations of biomarker responses. Finally, the use of biomarkers as a tool for biomonitoring and in situ assays was investigated, with discussion of advantages and disadvantages of their use. Environ. Toxicol. Chem. 2010;29:5-18. (C) 2009 SETAC